HIBAH HARTA BERSAMA KEPADA ANAK SETELAH PERCERAIAN (Studi Kasus Putusan No.436/Pdt.G/2009/PA.Mks) - Nur Hidayah (Al-'Adl, 2019)
One of the disputes that often occur as a result of divorce is shared marrital asset between husband and wife beside that cost of living for the child. This study aims to find out the position of marrital asset granted to children after the divorce and consideration of the judge in issuing a peace decision regarding the demands of child labor and sharing of marrital assets. This research was conducted in the Makassar 1A Religious Court, and the Law and islamic Faculty of the State Islamic University in the fiqh section. The type of research used was legal approach juridical research method, namely the approach to problems based on Islamic Law Compilation rules and existing interview data . Data obtained in the form of primary data and secondary data then analyzed qualitatively. Qualitative analysis is used to analyze data that is descriptive in nature including the results of interviews with judges in the Makassar Class 1A Religious Court, and lecturers at the Faculty of Law and Syariah State Islamic University in fiqh as well as from books that are relevant to the problem under study. The results obtained by this study include that in granting grants with objects that are donated are objects of shared assets that can be carried out on children. However, before determining the object to be granted first, the judge releases all charges or purifies the joint assets. After that, do the joint property grant. Grants made to children must also pay attention to the conditions for conducting grants and 1/3 of marrital assets. As for the sharing of marital asset assets which should be divided into two according to the Compilation of Islamic Law and Law No. 1 of 1974 can be flexed based on the conditions of the parties or agreements made.